Factor-inhibiting HIF-1 (FIH-1) is required for human vascular endothelial cell survival - Kiriakidis, S; Henze, A; Kruszynska-Ziaja, I; Skobridis, K; Theodorou, V; Paleolog, E; Mazzone, M (Federation of American Society of Experimental Biology, 2015)
Factor-inhibiting hypoxia-inducible factor (HIF)-1 (FIH-1) is an asparaginyl β-hydroxylase enzyme that was initially found to hydroxylate the HIF-α, preventing its transcriptional activity and leading to adaptive responses to hypoxia. More recently, other substrates, such as neurogenic locus notch homolog (Notch), have been found to be alternative FIH targets, but the biologic relevance of this regulation was never investigated. Given the key function of Notch in angiogenesis, we here investigate the role of FIH/Notch signaling in endothelial cells. We report that FIH-1 silencing in HUVECs results in reduced growth and increased apoptosis. The knockdown of FIH is associated with increased Notch2 activity, leading to enhanced expression of the Notch target hairy/enhancer-of-split related with YRPW motif protein 1 (Hey-1). Consistent with recent findings showing that Notch2 suppresses survivin (a key inhibitor of apoptosis), FIH targeting in HUVECs leads to selective repression of survivin in endothelial cells, thus promoting cell apoptosis and growth arrest. Our data support the concept that FIH-1 may interact with Notch2 and repress its activity, thereby playing a critical role in controlling the survival of vascular endothelial cells. These findings might pave the way toward novel, antiangiogenic strategies in disorders that are characterized by excessive vascular growth, such as cancer and rheumatoid arthritis.—Kiriakidis, S., Henze, A.-T., Kruszynska-Ziaja, I., Skobridis, K., Theodorou, V., Paleolog, E. M., Mazzone, M. Factor-inhibiting HIF-1 (FIH-1) is required for human vascular endothelial cell survival. FIH-1 was first identified in a yeast 2-hybrid screen for proteins that potentially interacted with the C-terminus of HIF-1α (1). In parallel studies, FIH-1 was shown to regulate transactivation of HIF-α by hydroxylation of an asparagine (Asn) residue in the HIF-α C-terminal transactivation domain (2, 3). HIF-α is a transcription factor that coordinates cellular responses in situations of reduced availability of oxygen (hypoxia), and activation of HIF-α signaling leads to extensive changes in gene expression to allow adaption of cells and tissues to reduced oxygenation (4, 5). The role of FIH-1 in HIF-α hydroxylation underlies the importance of this enzyme in angiogenesis, which plays a key function in many diseases, including cancer and rheumatoid arthritis (RA) (6, 7). The HIF complex consists of a constitutively expressed β subunit and an oxygen-responsive α subunit. Hydroxylation by FIH-1 of specific Asn residues in HIF-α (Asn803 in HIF-1α and Asn851 in HIF-2α) prevents recruitment of coactivators p300/cAMP response element-binding protein (CBP) and thereby, HIF-mediated gene transcription (1, 2). In contrast, prolyl hydroxylase domain (PHD) enzymes (PHD1–3) modify HIF-α by hydroxylation of specific proline residues in HIF-α (8), enabling capture by an E3 ubiquitin ligase complex whose recognition component is the von Hippel Lindau protein, leading to proteasomal destruction of HIF-α (9, 10). FIH-1 and PHD1–3 belong to a superfamily of 2-oxoglutarate and iron-dependent dioxygenases, which require molecular oxygen as a cosubstrate, explaining how these enzymes act as the oxygen sensors (11, 12). An important characteristic of FIH-1 is that unlike the PHD enzymes, FIH-1 is active even at relatively low oxygen levels (13–15). Whereas the role of FIH-1 in regard to HIF-α has been well characterized, increasing evidence suggests that HIF-α is not the only target for FIH-1, highlighting the importance of Asn hydroxylation as a means of posttranslational modification of intracellular proteins. A number of proteins have been identified as FIH-1 substrates, including members of the IκB family of proteins (16) and the intracellular domain (ICD) of the Notch transmembrane receptor (17). The discovery of alternative substrates for FIH-1 led to identification of the ankyrin repeat domain (ARD) as the common amino acid motif containing the Asn residues targeted by FIH-1. Hydroxylation of ARD at specific Asn residues within the p105 NF-κB precursor, the inhibitory proteins IκBα and IκBε, as well as in Notch proteins has been demonstrated (18). Recently, FIH-1 has been shown to regulate the survival of tumor cells via HIF-α-dependent and -independent mechanisms (19, 20). In the present study, we have investigated the role of FIH-1 in vascular endothelial cells by use of RNA interference (RNAi) approaches to determine whether FIH-1 also regulates the survival of endothelial cells. We observed that RNAi-mediated inhibition of FIH-1 resulted in reduced endothelial cell growth and increased apoptosis as a result of a decrease in expression levels of the key protective molecule survivin. As discussed, Notch proteins are a potential target for Asn hydroxylation by FIH-1 (18). Notch plays a pivotal role in vascular development and is required for arterial cell specification (21), as well as for tip and stalk cell specification during angiogenesis (22, 23). We demonstrated the use of a coimmunoprecipitation approach that FIH-1 is able to bind Notch2 in endothelial cells. Taken together, our findings suggest that FIH-1-driven modification of Asn within the ARD of Notch could play a role in endothelial cell function and thereby, in angiogenesis-dependent diseases, such as cancer and RA.